Pro-poor growth and pro-poor programs in Colombia (2005)
This paper analyzes the relationship between growth, poverty and income distribution using household data for Colombia for the years 1996 to 2004. We study the relationship between growth, inequality and poverty by following the Poverty Equivalent Growth Rate (PEGR) methodology developed by Kakwani and Khandker, which considers both the magnitude of growth and the degree to which the poor benefit from the growth process. We also carry out a decomposition of the changes in poverty to better understand the effects of growth, distribution and migration on poverty. Once we have explored pro-poor growth, we move on to study the pro-poorness of Colombia¿s main social programs using Kakwani and Son's "Pro-Poor Policy" index. The results show that growth in Colombia has generally been anti-poor, a consequence of high inequality in the urban sector and of low growth rates in the rural sector. Moreover, more than half of Colombia¿s social programs are also anti-poor, benefiting the non-poor to a larger extent than the poor.